KONTEN TIKTOK INDEPENDENT WOMAN MOTIVATION @YOURMOOD DAN PENINGKATAN SELF CONFIDENCE - Audri, Renada; Claretta, Dyva (Linimasa : Jurnal Ilmu Komunikasi, 2024)
Social media is capable of spreading information quickly due to the presence of the internet. The TikTok application, in addition to being used for video editing, can also be used to present educational and motivational content through short video clips. This research aims to determine the extent of the influence of TikTok content @Yourmood and self-confidence on followers. The theory used in this study is the Stimulus-Organism-Response theory. This research adopts a quantitative approach. The sampling technique used is non-probability sampling, specifically accidental sampling, with a sample size of 100 respondents. Data collection is conducted through a questionnaire. The research is analyzed using descriptive statistics, linearity tests, normality tests, heteroskedasticity tests, simple linear regression analysis, coefficient of determination, and correlation tests using SPSS. The results of the research indicate an influence of TikTok content, Independent Woman Motivation @Yourmood, on the improvement of self-confidence by 56.4%, which is of moderate significance. This means that the content of TikTok @Yourmood does not account for the total influence on the improvement of self-confidence by any other factors.